ANALYSIS OF HOUSEHOLDS’ SUGAR CONSUMPTION PATTERN IN BAUCHI STATE NIGERIA - Mohammed, R.; Usman, A. B.; Hamidu, K.; Shehu, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined household sugar consumption patterns in Bauchi State, Nigeria. Cross-sectional data were collected from 412 households through a multi-stage sampling technique. The data were analyzed using descriptive statistics and a linear regression model. The result revealed that the mean age of the respondents was 46.71 in the northern zone, 46.75 in the central zone, and 49.7 in the western zone. Most (90.2%,94.2%, and 87.9%) of the household heads in the northern, central, and western zones respectively were male and married, with 87.4% in the north zone, 94.2% in the central zone and 89.7% in the western zone. The mean household size was 11 persons in the northern zone, 10 persons in the central zone, and 9 persons in the western zone. The study further reveals that the respondents (65.7%,45.2%, and 47.9%) in northern, central, and western zones consume sugar every day respectively. The socio-economic factors influencing sugar consumption were average monthly income (P<0.01), cost of a kilogram of sugar(P<0.05), household size (P<0.01), age of the household head (P<0.05), community of the respondents (P<0.05), average monthly food expenditure (P<0.05) were all significant in influencing household sugar consumption, with an R2 value of 0.505 and the F-value was (33.889) significant (P<0.01). The research concluded that socioeconomic factors have an influence on the sugar consumption pattern of households. The research, therefore, provides data for firms and individuals who wish to invest in the sugar market to develop suitable business strategies. The study, therefore, recommended implementing an adequate policy that will reduce the cost of sugar production and increase the supply. Household income should also be increased to enable the households to meet the demand for their food necessities like sugar and invariably enhance the living standard of the respondents.